Enzyme activity of zhargalant farm soil, central province of Mongolia - J, Bayarmaa; D, Purev (Mongolian Journal of Agricultural Sciences, 2018)
We conducted monitoring analysis of cellulase, saccharase, protease, urease, acid and alcaline phosphatase activities of Zhargalant farm soil, Central province of Mongolia. From the results it is clear seen that for the year activity of cellulase, protease and urease are increased but activity of saccharase decreased. The activity of acid phosphatase on control, wheat and nearby wheat field soils decreased but on rape and nearby rape fields its activity increased. About alkaline phosphatase its activity decreased on control and soil of wheat field, on soils of nearby wheat, rape and nearby rape fields its activity increased. For the field where seeding crops did not produces there was positive correlation between humus and enzyme activity, but for the soils were the crops were sown this correlation changes depending on the enzymes. This trend is also observed for the soils of nearby fields.